2006
DOI: 10.1079/phn2005870
|View full text |Cite
|
Sign up to set email alerts
|

Saturated fat in the diet of Spanish children: relationship with anthropometric, alimentary, nutritional and lipid profiles

Abstract: Objective: To compare the anthropometric, alimentary, nutritional and lipid profiles and global diet quality of Spanish children according to saturated fat intake. Design: This was a cross-sectional study. Food data were collected using a foodfrequency questionnaire. Subjects and methods: The sample included 1112 children of both sexes, aged between 6 and 7 years, selected by means of random cluster sampling in schools. The plasma lipid profile included measurements of low-density lipoprotein cholesterol (LDL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…This finding contrasts with previous research in Spanish children that found a positive correlation between a dietary variety index and plasma lycopene concentrations (r = 0.27, adjusted for energy intake) (29). Although a high intake of tomatoes may be characteristic of dietary patterns that are rich in vegetables in Mediterranean populations, this relation may not be comparable in Australian population groups.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…This finding contrasts with previous research in Spanish children that found a positive correlation between a dietary variety index and plasma lycopene concentrations (r = 0.27, adjusted for energy intake) (29). Although a high intake of tomatoes may be characteristic of dietary patterns that are rich in vegetables in Mediterranean populations, this relation may not be comparable in Australian population groups.…”
Section: Discussioncontrasting
confidence: 98%
“…In adult populations, associations between diet quality and lipid profile have been observed in the expected direction (3). However, in child populations, no studies observed significant associations between diet quality and serum lipid profile (29,33). There may be a number of reasons why the validation of diet quality indexes in relation to markers of disease status or risk in children is particularly difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Participants with the highest adherence had fewer possibilities of having low HDL-C than those in the lowest quartile [59]. In children, consuming diets with less SFA was also associated with better LDL-C/HDL-C and APOB/APOA1 ratios [60]. These epidemiological studies of Mediterranean diets do not provide direct evidence of olive oil influence and should be evaluated with caution considering that adherence indices included consumption of fish, fruit, grains, legumes, nuts, vegetables, and wine in addition to olive oil.…”
Section: Epidemiological Studiesmentioning
confidence: 93%
“…The progressive globalization of food products seems to have contributed to the decline of traditional healthy food choices (Aravanis et al, 1988;Hassapidou et al, 2006;Petridou et al, 1995;Royo-Bordonada et al, 2006). Studies in pediatric samples exploring adherence to the MD are scarce.…”
Section: Introductionmentioning
confidence: 99%